1985
DOI: 10.1128/jvi.55.2.264-273.1985
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial murine cytomegalovirus pneumonia after irradiation: characterization of cells that limit viral replication during established infection of the lungs

Abstract: Interstitial pneumonia associated with viral replication in lung tissue was observed after cytomegalovirus infection of total-body y-irradiated mice, whereas in noncompromised hosts the lungs were not affected and virus multiplication was restricted to the salivary glands. The radiation damage could either predispose normally nonpermissive cell types for productive infection or abrogate an immune control of the tissue manifestation of infection by elimination of lymphocytes. Adoptive transfer of lymphoid cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
198
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(211 citation statements)
references
References 44 publications
13
198
0
Order By: Relevance
“…Prolonged immune responses within the brain following MCMV infection are characterized by persistence of antibody-producing B-cells, chronic microglial cell activation, and retention of MCMV-specific effector-memory CD8 1 T-cells (Mutnal et al, 2011b;Mutnal et al, 2012). Although CD8 1 T-cells play an important role in controlling acute brain infection (Reddehase et al, 1987(Reddehase et al, , 1985, the chronic presence of these IFN-g-producing T-cells may be damaging to the brain. Although retention of antigen-specific CD8 1 T-cells following MCMV infection helps to protect against virus reactivation, they are also responsible for long-term activation of microglia throughout the brain (Mutnal et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged immune responses within the brain following MCMV infection are characterized by persistence of antibody-producing B-cells, chronic microglial cell activation, and retention of MCMV-specific effector-memory CD8 1 T-cells (Mutnal et al, 2011b;Mutnal et al, 2012). Although CD8 1 T-cells play an important role in controlling acute brain infection (Reddehase et al, 1987(Reddehase et al, , 1985, the chronic presence of these IFN-g-producing T-cells may be damaging to the brain. Although retention of antigen-specific CD8 1 T-cells following MCMV infection helps to protect against virus reactivation, they are also responsible for long-term activation of microglia throughout the brain (Mutnal et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes are known to be the primary effector cells capable of defending many tissues from productive CMV infection (Jonjic et al, 1989;Koszinowski et al, 1990;Reddehase et al, 1985), but when operating within the CNS, cytotoxic destruction of infected target cells may induce irreparable brain damage. The present study was undertaken to determine which T-cell subset is responsible for mediating the suppressive effect of adoptive transfer in our brain infection model and to determine the effector mechanism(s) used by these lymphocytes to control MCMV infection of the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Continued administration of CP, however, leads to an increased virus replication in the lung, but appears to prevent cellular in¢ltration and interstitial pneumonitis, presumably because the immunological process required is now also suppressed. In a third model, interstitial pneumonitis associated with viral replication was evident in lung tissue after MCMV infection in total body Qirradiated mice [99]. Finally, latently infected mice given a single injection of anti-CD3 monoclonal antibody to activate their T-cells developed a fatal interstitial pneumonia 24^48 h post injection [261].…”
Section: Damagementioning
confidence: 98%
“…Recovery from CMV disease, however, correlates with a cellular immune response. Early work by Koszinowski and colleagues using adoptive transfer experiments in susceptible BALB/c mice demonstrated that T lymphocytes limit the viral replication and prevent histopathology [99]. Moreover, CD8 cytotoxic T lymphocytes (CTLs) generated in BALB/c mice were directed against both structural and non-structural viral proteins, although a major fraction was speci¢c for antigens expressed at IE times during infection [100^105].…”
Section: The Immune Responsementioning
confidence: 99%